THE RELATIONSHIP BETWEEN THE VARIATION OF LEARNING MEDIA USE AND THE LEARNING MOTIVATION OF PACKAGE B STUDENTS AT PKBM FARILLA ILMI, PADANG CITY - Febrina Laraswati, Rheka; Solfema, Solfema (Universitas Negeri Padang, 2023)
ABSTRACT The relationship between PKBM Farilla Ilmi Package B students in Padang City varies the use of learning media and learning motivation. Thesis of the Faculty of Education, Padang State University. It is the motivation of students studying who take part in package B PKBM Farilla Ilmi learning in Padang City that is the background for making this essay. The purpose of this study was to examine data on the use of different learning media and the motivation of Package B students at PKBM and to understand the relationship between these two factors at PKBM Farilla Ilmi, Padang City. This type of research is a type of national quantitative research that looks at the interaction between various types of learning media and the learning motivation of package B students at PKBM Farilla Ilmi, Padang City. The data analysis technique uses percentage and sperman rho techniques to display the images of the two variables and their respective relationships. With a population of 40 people and a sample of 28 people, 70% of the population was selected. The research findings show that: (1) There are many variations in the use of educational media; (2) There are many variations on how students are motivated; and (3) there is a positive and significant relationship between these variations and student learning outcomes. motivation to join PKBM for Farilla Ilmi Package B Students, Padang City. It is suggested to: (1) Educators or tutors to be able to add a variety of learning media to package B, (2) PKBM administrators pay more attention and provide suggestions for developing variations of learning media in PKBM, and (3) Future researchers to be able to identify other characteristics or variables that related to learning motivation. Keywords: Learning Media, Learning Motivation, PKBM